he Effect of Adding Cotton Meal and Soy Bean Meal on Glucose and total Blood Protein Serum of Shami Goat Kids (Journal of Hama University, 2021)
The study was conducted on 18 Shami goat Kids in the Agricultural Scientific Research Center in Hama, their age was 150 days, to ages and weights, reaching an average of 23.2kg, and they were dived into three groups(6 per group) depending on the source of the protein included in the composition. The died for each of them 14%(as a 100% unshelled cotton gain for the first group, 100% soybean gain for the second group, a 50% unpeeled cotton gain and 50% soybean gain for the third group). Blood samples from the jugular vein were collected from all test subjects before starting feeding on the feed. Watch after one, two and three months from the start of feeding. Gifts blood samples were analyzed in all groups and a study of the indicators of glucose, general protein, albumin and globulin in blood serum to assess the energy and protein metabolism of gifts, when feeding on these diets. The results showed a significant increase (ᴘ≤0.05) in the concentration of glucose in gifts after two months of experience in the three groups, but this was the highest increase in the second group versus the control and the first and third groups, then its concentration decreased after that. A significant increase (ᴘ≤0.05) was observed with the concentration of the total protein in the blood serum after a month of the experiment. The total protein concentration decreased after three months in the blood kids in second and third groups compared with the first and control groups. The albumin concentration decreased after two months (ᴘ≤0.05) in the first group compared with second, third and control, also it's decreased after three months in the first and third groups compared with the second and control. The globulin concentration in the blood serum increased after one month in the three groups compared with the control, then in two months decreased( not significant) in the three groups, and after three months decreased (ᴘ≤0.05) the globulin concentration in the second and third groups.The increase in the weights of gift items in the groups was respectively: the first group 9.45kg (95g ∕ day), the second group 13.6kg (136g ∕day) and the third group 10.45kg (106g ∕day). We conclude that the energy and protein metabolic indicators were the best in the second group feeding 100% soybean meal as a protein source, which can reduce the period for fattening gifts and reflect positively on economic side and income generation.